Measurements of Soil Surface Roughness During the Fourth Microwave Water and Energy Balance Experiment: April 18 through June 13, 2005 - Mi-joung Jang; Kai-Jen Calvin Tien; Joaquin Casanova; Jasmeet Judge (EDIS, 2019)
Passive microwave signatures have been used to retrieve geophysical parameters, such as soil temperature [Njoku and Li, 1999], moisture [Jackson et al., 1995], and surface roughness [Wegmüller and Mätzler, 1999]. One of the challenges in the parameter retrieval is the effect of soil surface roughness on the microwave emission. We conducted soil surface roughness measurements as part of our fourth Microwave Water and Energy Balance Experiment (MicroWEX-4) to understand the effects of surface roughness on microwave signatures at 6.7 GHz (λ = 4.48 cm). The dataset will also be used to develop and validate surface roughness models. In this report, we summarize briefly the theoretical background of surface roughness characteristics and discuss methodology and results of the roughness experiments. This document is Circular 1483, one of a series of the Department of Agricultural and Biological Engineering, UF/IFAS Extension. Original publication date November 2005.